2010
DOI: 10.4103/0973-1482.65246
|View full text |Cite
|
Sign up to set email alerts
|

Coexisting intracranial tumors with pituitary adenomas: Genetic association or coincidence?

Abstract: The co-occurrence of two or more brain tumors with different histological features is rare. The authors report three rare cases of intracranial tumors associated with pituitary adenomas. Two of the pituitary tumors were functioning adenomas: a prolactinoma and a thyrotropin secreting adenoma. Two of the associated intracranial neoplasms were gliomas and one was a meningioma. Radiological and clinical examination for syndromal association was negative in all cases. We briefly discuss the presentation and treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 12 publications
1
39
0
Order By: Relevance
“…Furthermore, in neurofibroma (type 2), a mutation in NF2, a tumor suppressor gene located at chromosome position 22q12, has been associated with the formation of various intracranial tumors, including meningiomas, gliomas and vestibular schwannomas (16). In addition, Furtado et al (11,15) reported three cases of pituitary adenoma associated with two cases of glioma and one case of meningioma, and demonstrated that these tumors resulted from gene mutations common to both tumor types in each case. However, various gene mutations have been identified in pituitary adenomas and other intracranial tumors, such as gliomas and meningiomas, that have different roles in each tumor type.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, in neurofibroma (type 2), a mutation in NF2, a tumor suppressor gene located at chromosome position 22q12, has been associated with the formation of various intracranial tumors, including meningiomas, gliomas and vestibular schwannomas (16). In addition, Furtado et al (11,15) reported three cases of pituitary adenoma associated with two cases of glioma and one case of meningioma, and demonstrated that these tumors resulted from gene mutations common to both tumor types in each case. However, various gene mutations have been identified in pituitary adenomas and other intracranial tumors, such as gliomas and meningiomas, that have different roles in each tumor type.…”
Section: Discussionmentioning
confidence: 99%
“…Amit et al (6) and Furtado et al (11) have previously speculated that different intracranial tumors may originate from cellular remnants left following embryogenesis. This hypothesis appears to be supported by a case of craniopharyngioma associated with pituitary adenoma and notochordoma reported by Shishkina et al (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The coexistence of PA and another type of brain tumor is a very rare clinical scenario (4,5). The type of PAs reported in such series varied from, clinically silent lesions "non-functional" to functioning adenomas such as prolactinomas and growth hormone (GH)-and thyrotropin (TSH)-secreting tumors (1,4,(6)(7)(8)(9). In cases of PA concurrent with meningioma, GH-secreting adenoma is the most predominant (9)(10)(11).…”
Section: Background and Importancementioning
confidence: 99%
“…Concomitant brain tumor and association of PA with other tumors comprise 15−25% of all intracranial neoplasms with an annual incidence of 6/100,000 (1). Pituitary adenomas (PAs) are very common benign neoplasms, with a prevalence of 10 to 23% in unselected adult population considering population surveys, radiological, and autopsy series (2,3).…”
Section: Background and Importancementioning
confidence: 99%